Standard Gamble to Derive Utility Health States for Limbal Stem Cell Deficiency - Smith AB; Retzler J; Taylor MJ (ClinicoEconomics and Outcomes Research, 2020)
Adam B Smith, Jenny Retzler, Matthew J Taylor York Health Economics Consortium Ltd, University of York, York YO10 5NQ, UKCorrespondence: Adam B SmithYork Health Economics Consortium Ltd., Enterprise House, Innovation Way, University of York, York YO10 5NQ, United KingdomTel +44 1904 363220Fax +44 1904 323628Email adam.smith@york.ac.ukPurpose: To generate UK health-related quality-of-life (HRQoL) data for adult patients with moderate-to-severe limbal stem cell deficiency (LSCD), unilateral or bilateral, due to physical or chemical ocular burns to help inform economic evaluations of treatments.Patients and Methods: EQ-5D-3L with vision bolt-on scores was prospectively measured for one of five clinical scenarios of LSCD described in vignettes in a demographically representative population of 520 UK adults. These were converted to health state utilities using three different UK value sets. A standard gamble (SG) was then undertaken using 12 SG scenarios to examine the component drivers of health utility for the treatment of LSCD.Results: For the EQ-5D-3L scenarios, the mean disutility for LSCD with poor visual acuity, pain and disfigurement in both eyes compared to one eye was − 0.084 (range=− 0.156 to − 0.045 across the value sets). The mean disutility of bilateral LSCD with pain, disfigurement, and poor visual acuity compared to unilateral LSCD with only poor visual acuity in one eye was − 0.104 (range=− 0.151 to − 0.078). Similarly, where one eye was affected, pain and disfigurement in combination were associated with a greater mean disutility than improvements in visual acuity alone: − 0.011 (range=− 0.04 to 0.005). Mean SG utilities were within a narrow range (0.682– 0.765). Where one eye was affected, the main driver was disfigurement: mean utility was 0.731 (0.709– 0.753) compared to 0.682 (0.659– 0.704) when disfigurement was removed compared to vision restored to normal. For bilateral LSCD, mean utilities were 0.693 (0.672– 0.715) for normal vision and 0.75 (0.73– 0.771) when disfigurement and pain were removed.Conclusion: Improvements in pain and disfigurement appeared to be the main factors driving differences in health utilities associated with symptom profiles in LSCD, with improvements in visual acuity having lesser impact.Keywords: standard gamble, utility states, limbal stem cell deficiency, LSCD, ocular burns, holoclar®